A distinct CD38+CD45RA+ population of CD4+, CD8+, and double-negative T cells is controlled by FAS - Maccari, Maria Elena; Fuchs, Sebastian; Kury, Patrick; Andrieux, Geoffroy; Bengsch, Bertram; Lorenz, Myriam Ricarda; Heeg, Maximilian; Rohr, Jan; Jägle, Sabine; Castro, Carla N.; Groß, Miriam; Warthorst, Ursula; et al. (Journal of Experimental Medicine, 2021)
The identification and characterization of rare immune cell populations in humans can be facilitated by their growth advantage in the context of specific genetic diseases. Here, we use autoimmune lymphoproliferative syndrome to identify a population of FAS-controlled TCRαβ+ T cells. They include CD4+, CD8+, and double-negative T cells and can be defined by a CD38+CD45RA+T-BET- expression pattern. These unconventional T cells are present in healthy individuals, are generated before birth, are enriched in lymphoid tissue, and do not expand during acute viral infection. They are characterized by a unique molecular signature that is unambiguously different from other known T cell differentiation subsets and independent of CD4 or CD8 expression. Functionally, FAS-controlled T cells represent highly proliferative, noncytotoxic T cells with an IL-10 cytokine bias. Mechanistically, regulation of this physiological population is mediated by FAS and CTLA4 signaling, and its survival is enhanced by mTOR and STAT3 signals. Genetic alterations in these pathways result in expansion of FAS-controlled T cells, which can cause significant lymphoproliferative disease.
CRIS-Team Scopus Importer:2020-12-18